A Comparative Study on Structural Growth of Copper Oxide Deposited by dc-MS and HiPIMS. (1st January 2016) - Kunti, Arup Kumar; Sharma, Shailendra Kumar; Gupta, Mukul
Abstract : In this article, copper oxide films are deposited on glass substrate at room temperature by reactive dc-magnetron sputtering (dc-MS) and high power impulse magnetron sputtering (HiPIMS) at different oxygen flow ratio (OFR). Structural properties and orientation process of films changes with the variation of oxygen flow ratio (OFR) in both the systems. Pure Cu to CuO phase transformation was observed as the OFR was increased. Following (111) preferred orientation of Cu and Cu2 O mixed phase was observed upto 15% and 30% OFR in the dc-MS and HiPIMS deposited films. In dc- MS, CuO phase was achieved at 50% OFR but more oxygen needed to grow CuO phase for HiPIMS. d-spacing of films deposited by dc-MS increased at high OFR, whereas films deposited by HiPIMS showed opposite trends. Crystallinity of films increased with increasing OFR. Crystallite size of films increased after annealing. Interplaner spacing of Cu2 O/CuO increased after annealing. It infers that unit cell of films increased after annealing as interplanar distance increased. Atomic force microscopy shows that surface morphology of the films influenced by the variation of OFR.